2007
DOI: 10.2209/tdcpublication.48.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cevimeline on Radiation-Induced Salivary Gland Dysfunction and AQP5 in Submandibular Gland in Mice

Abstract: The aim of this study was to clarify the effects of the muscarinic receptor agonist, cevimeline, on saliva flow and expression of aquaporin5 (AQP5) in submandibular gland after X-ray irradiation. Using a previously established radiation-induced xerostomia model mouse, saliva flow from at 7 days before irradiation to at 28 days after irradiation was investigated in mice that were treated with cevimeline before or after irradiation. Radiation caused a significant decrease in saliva flow compared with nonirradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…Such extensive salivary gland fibrosis results in diminished saliva production, which leads to numerous morbidities in patients, including dysphagia, increased oral infections (e.g., Candidiasis, dental caries), as well as generalized oral discomfort. Radiation additionally causes a down-regulation of AQP5 expression in the salivary gland of rats and mice, with similar reductions in AQP5 staining to those we herein have noted in the β1 glo /MC mice (37, 38). The β1 glo /MC mice, therefore, seem to mimic the process of salivary gland fibrosis seen in pathological conditions such as radiation induced injury and may be a useful model to investigate early interventions to treat fibrosis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Such extensive salivary gland fibrosis results in diminished saliva production, which leads to numerous morbidities in patients, including dysphagia, increased oral infections (e.g., Candidiasis, dental caries), as well as generalized oral discomfort. Radiation additionally causes a down-regulation of AQP5 expression in the salivary gland of rats and mice, with similar reductions in AQP5 staining to those we herein have noted in the β1 glo /MC mice (37, 38). The β1 glo /MC mice, therefore, seem to mimic the process of salivary gland fibrosis seen in pathological conditions such as radiation induced injury and may be a useful model to investigate early interventions to treat fibrosis.…”
Section: Discussionsupporting
confidence: 86%
“…Reduced levels of AQP5 lead to decreased saliva secretion and salivary gland hypofunction (27, 28). Interestingly, down-regulation of AQP5 can be caused by radiation-induced injury to the salivary gland (37, 38) and radiation damage can to lead to increased TGF-β1 expression (16). Although AQP5 also plays an important role in pulmonary secretions, the β1 glo /MC mice did not show altered expression or trafficking of AQP5 in the lungs (data not shown), suggesting that the MMTV-Cre transgenic line is limiting recombination mediated TGF-β1 expression primarily to the salivary gland.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier hypothesis suggested that the secretory granules of acinar cells are damaged by radiation-induced lipid peroxidation, which leads to the generation of free radicals and lysis of these cells (Nagler et al , 1997). While the administration of muscarinic or adrenergic agonists, which trigger degranulation of secretory cells, prior to radiation (15 Gy) has been shown to maintain partial salivary flow in rats and mice (Nagler et al , 1997; Nagler and Laufer, 1998; Coppes et al , 2000; Takakura et al , 2007), not all clinical studies have corroborated these effects (Roesink et al , 2004). Down-regulation of aquaporin-5 (AQP5), a water channel present on the apical membrane of acinar cells, has been observed in rat submandibular glands on days 3 and 30 after a single 15-Gy dose (Li et al , 2006).…”
Section: Mechanisms Of Sensitivitymentioning
confidence: 99%
“…The typical fraction size (~ 2 Gy) in affected individuals is provided at the top as a reference for the other models. Physiological, molecular, and histological changes are graphed relative to the single radiation dose evaluated in the rat, mouse, miniature pig, and rhesus monkey models (Stephens et al , 1986a,b, 1991; Vissink et al , 1990; Nagler, 1998; Nagler et al , 1998; Paardekooper et al , 1998; Bralic et al , 2005; Konings et al , 2005a, 2006; Li et al , 2005; Humphries et al , 2006; Limesand et al , 2006; Muhvic-Urek et al , 2006;Takakura et al , 2007; Avila et al , 2009). …”
Section: Figuresmentioning
confidence: 99%
“…Another major cause of xerostomia is radiation-induced salivary gland dysfunction. The expression of AQP5 and its distribution in the salivary glands is reported to be altered by irradiation [3, 31, 32]. It would be difficult, however, to elucidate whether these changes in AQP5 expression and distribution are directly related to the reduced salivary secretion in Sjögren’s syndrome or radiation-induced xerostomia because the physiological importance of AQP5 in salivary secretion is still unclear.…”
Section: Aqp5 and Human Diseasementioning
confidence: 99%